PENGARUH EPS, ROE, ROA DAN DER TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR SEMEN YANG TERDAFTAR DI BEI - Asep Alipudin (Universitas Pakuan, 2016)
The purpose of this study was to determine the effect of earnings per share (EPS), return on equity (ROE), return on assets (ROA) and debt to equity ratio (DER) to the price of shares in the sub-sector of cement which is listed on the Stock Exchange simultaneously. There is also the test used is the classic assumption test, test the coefficient of determination, t test, and F test results show earnings per share (EPS), return on equity (ROE), return on assets (ROA) and debt to equity ratio (DER) jointly positive effect on stock prices at a cement company listed on the Indonesia stock Exchange (BEI) in the period 2010-2014.Keywords: Earning per Share (EPS), Return on Equity (ROE), Return on Assets (ROA), dan Debt to Equity Ratio (DER)